AN ALTERNATIVE PROCEDURE FOR THE 18O MEASUREMENT OF NITRATE OXYGEN - Brauer K.; Strauch G. (My University, 2000)
A new method for the preparation of nitrate samples for 18O measurement is presented. The technique utilizes guanidine hydrochloride to convert the nitrate oxygen to CO2. The δ18O values of our KNO3 laboratory standard (K1) obtained by the guanidine method are compared with the results of the reaction of the potassium nitrate laboratory standard K1 with mercury cyanide and with the silver nitrate-graphite method. The δ18O data produced by the high temperature (900°C) cyanide and graphite technique are comparable to the guanidine method only when the potassium nitrate is converted to silver nitrate.The reproducibility for the guanidine method is +/-0.2%% based on the tests carried out using KNO3 (laboratory standard, K1) and the IAEA-N3 reference material. The yield of the conversion of nitrate oxygen to CO2 is 95-100%.
Keywords: CARBON DIOXIDE; ISOTOPE FRACTIONATION; NITRATE; OXYGEN ISOTOPES